How does the welfare state reduce crime? The effect of program characteristics and decommodification across 18 OECD-countries. (May 2020) - Rudolph, Maximilian; Starke, Peter
Abstract: Purpose: The article revisits the negative effect of welfare state schemes on crime rates with a focus on the pathways of that effect. Social support theory (SST) and institutional anomie theory (IAT) are two related theoretical approaches to explain why – and how – the welfare state might prevent criminal behavior. This article tests the relevance of these theories for cross-country and over-time variation in homicide rates with more precise disaggregated welfare state indicators than used previously. Methods: We use panel regressions with country fixed effects and data for 18 OECD countries between 1990 and 2011. Disaggregated cross-national social expenditure and benefit generosity data is used to discriminate between pathways of welfare state influence on cross-national homicide. Results: The welfare state suppresses crime particularly through social support via generous unemployment benefits. Overall decommodification, the key measure to test IAT, however, does not have any effect on homicide. Conclusions: Only some welfare state interventions matter for homicide rates. Highlights: Homicide rates are associated with differences in welfare state size and generosity. Unemployment benefit generosity has a clear negative impact across 18 countries. Differences in decommodification do not matter, contrary to previous studies. This suggests that government support via specific schemes can help lower crime.